(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Antimicrobial resistance is a global health threat, driven in large part by irrational antibiotic prescribing in hospitals. Antibiotic stewardship programs (ASPs) are evidence-based strategies to optimize antibiotic use, reduce resistance, and improve patient outcomes. This study evaluated the impact of an antibiotic stewardship intervention on antibiotic consumption and health-care-associated infection (HAI) rates at Ch. Pervaiz Elahi Institute of Cardiology, Multan. Methods: A prospective interventional study was conducted on 300 patients admitted between January and June 2025. Patients were divided into two groups: pre-intervention (n=150) and post-intervention (n=150). The stewardship program included prescriber education, guideline dissemination, and audit-feedback mechanisms. Outcomes assessed included antibiotic consumption, appropriateness of prescribing, and incidence of HAIs. Data were analyzed using chi-square and t-tests, with p<0.05 considered significant. Results: The average number of antibiotic prescriptions per patient declined from 2.4 in the pre-intervention phase to 1.7 in the post-intervention phase (p<0.01). Use of carbapenems decreased significantly from 30.0% to 14.0%, while third-generation cephalosporin use declined from 36.0% to 26.0%. Inappropriate prescriptions were reduced from 44.7% to 20.0% (p<0.001). HAI incidence decreased from 8.0% (12/150) in the pre-intervention group to 3.3% (5/150) in the post-intervention group (p=0.04). No significant differences were observed in mortality (4.0% vs. 3.3%) or mean hospital stay (6.8 vs. 6.5 days). Conclusion: The stewardship intervention led to substantial improvements in antibiotic prescribing and a reduction in HAIs without adverse effects on patient safety. Sustained ASP implementation is recommended to combat antimicrobial resistance and enhance patient outcomes in resource-limited hospital settings.